Inovasi Produk Sosis Kelinci sebagai Hilirisasi Usaha bagi Kelompok Ternak Kelinci Aza Akmal Rabbit Farm di Kabupaten Kendal - Siti Susanti; Ahmad Ni’matullah Al-Baarri; Heni Rizqiati; Yasmin Aulia Rachma; Haristi Uswatun Nisa (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Rabbits are easily adaptable and reproduce quickly, providing benefits to breeders. Kendal Regency is one of the areas in Central Java Province that has potential in the field of rabbit farming. One of the rabbit farming groups in Kendal Regency is the Aza Akmal Rabbit Farm, which develops New Zealand rabbits. The high number of rabbits is inversely proportional to the low market demand; thus, the marketing of rabbit meat is still limited to frozen carcasses. This is influenced by the lack of knowledge of breeders regarding the processing and marketing of rabbit meat products. The purpose of the community service activity was to provide education related to the importance of product innovation and how to process rabbit sausages to increase community income. The method used was direct skills training, and the level of preference was evaluated using a hedonic test on 25 panelists. The results of the activity were in the form of a brownish-white rabbit sausage product, with a distinctive aroma and taste of rabbit sausage, and a compact and chewy texture. The results of the hedonic test of the color parameters were quite liked, aroma liked, texture liked, taste liked, and overall liked. In conclusion, community service activities can add new knowledge related to processing rabbit sausages. The hedonic test results showed that the panelists liked the rabbit sausages, indicating their potential for development to improve the community's economy.